Quality Improvement at an Academic Cancer Center: Venous Thromboembolism Prophylaxis in Patients With Multiple Myeloma - Rachid Baz MD; Roy Furman MD, PhD; Katherine Simondsen PharmD, BCOP; Christine Stone PhD, MBA (Cancer Control, 2020)
Patients with multiple myeloma are at elevated risk of venous thromboembolism (VTE), the second leading cause of death in patients with cancer, but physician adherence to VTE prevention guidelines is low. Several organizations partnered in designing and implementing a 2-year quality improvement (QI) program in a tertiary care/academic cancer center, to increase awareness of VTE prophylaxis for patients with multiple myeloma and thus improve adherence to prophylaxis guidelines and protocols. The QI arm included 2 chart audits, conducted 2 years apart, of unmatched cohorts of 100 patients with multiple myeloma. An Education arm included 2 grand rounds presentations, 3 web-based case discussions, and a patient education module. Twenty providers took part in the continuous QI arm. More than 1100 learners participated in the online cases; the patient education curriculum reached 112 multiple myeloma patients. The initiative proved helpful in defining barriers to guideline adherence and identifying data-driven practice improvement strategies for VTE prophylaxis. It also increased learner awareness of VTE guidelines, patient risk stratification, and optimal thromboprophylaxis strategies. There was a reduction in VTE events (primary clinical outcome) from 10% at baseline to 4% in the follow-up cohort, although this was not statistically significant. Higher rates of guideline-based prophylaxis were observed in low-risk patients, and a lower incidence of VTE was observed in multiple myeloma patients with a prior history of VTE. Additional research is needed to refine prophylaxis guidelines. With appropriate institutional support, this type of QI program can be readily adopted by other organizations to address practice improvement needs.